Acts and Laws of His Majesty's Province of New Hampshire in New England 63 (1761) - (:unkn) unknown (My University, 1759)
An Act About Powdr Money, § 1: That every foreign ship or vessel above thirty tons, coming into any port or part of this province from over the sea to trade or traffick [sic], all or the major part of the owners whereof are not actually inhabitants of this province, shall, every voyage they make, pay two shillings in money per ton, or one pound of good gunpowder
Keywords: GUNPOWDER - TRANSPORTATION